Pengembangan Modul Bilingual Bergambar dengan Pendekatan Realistic Mathematics Education (RME) pada Materi Himpunan - Nurfithriyya, Aida; Kesuma, Guntur Cahaya; M, Rosida Rakhmawati (Indonesian Journal of Science and Mathematics Education, 2020)
Abstract: The purpose of this reaserch is to develop teaching materials consisting of pictorial bilingual modules using Realistic Mathematics Education (RME) on set material and to research the effectiveness of the product being developed. The research used in this research is Research and Development using ADDIE models consisting of motion sickness Analysis, Design, Development, Implementation and Evaluation. This study was declared valid and feasible to be used as teaching material for mathematics learning by 3 material experts who obtained an average score of 3,72 in the "valid" category and 3 media experts with an average score of 3,71 in the "valid" category and 3 language experts with an average score of 3,65 with the category of "Valid" with each maximum score of validity is 4. With the test of attractiveness of teaching materials determined "Very Attractive" by a small group test of 9 students by agreeing to the average score average of 3,65 and a large group test of 29 students with approval of an average value of 3,68. The results of the assessment using testing the effect size with an approval score of 0,50 with the category "Effective Enough". So it can be concluded that the development of teaching materials produced is declared feasible and effective enough and can be used as teaching materials in learning mathematics. Abstrak: Tujuan dari penelitian ini yaitu mengembangkan bahan ajar berupa modul bilingual bergambar dengan pendekatan Realistic Mathematics Education (RME) pada materi himpunan serta mengetahui keefektifitasanproduk yang dikembangkan. Penelitian yang digunakan dalam penelitian ini adalahResearch and Development menggunakan model ADDIE yang terdiri dari tahap Analyze, Design, Development, Implementation dan Evaluation. Penelitian ini dinyatakan valid dan layak digunakan secara keseluruhan sebagai bahan ajar pembelajaran matematika oleh 3 ahli materi yang memperoleh skor rata-rata sebesar 3,72 dengan kategori “valid” dan 3 ahli media dengan skor rata-rata sebesar 3,71 dengan kategori “valid” serta 3 ahli bahasa dengan skor rata-rata sebesar 3,65 dengan kategori “Valid” dengan masing-masing skor maksimal kevalidan adalah 4. Sedangkan uji kemenarikan bahan ajar dinyatakan “Sangat Menarik” oleh uji kelompok kecil terhadap 9 orang peserta didikdengan perolehan skor rata-rata sebesar 3,65 dan uji kelompok besar terhadap 29 orang peserta didik dengan perolehan nilai rata-rata sebesar 3,68. Hasil penilaian uji efektivitas dengan menggunakan rumus effect sizedengan perolehan skor sebesar 0,50 dengan kategori “Cukup Efektif”. Sehingga dapat disimpulkan pengembangan bahan ajar yang dihasilkan dinyatakan layak dan cukup efektif serta dapat digunakan sebagai bahan ajar dalam pembelajaran matematika.